Intraindividual Coupling of Daily Stressors and Cognitive Interference in Old Age - Stawski, Robert S. (Oxford University Press, 2011)
OBJECTIVES. The current study examined emotional and cognitive reactions to daily stress. We examined the psychometric properties of a short cognitive interference measure and how cognitive interference was associated with measures of daily stress and negative affect (NA) between persons and within persons over time. METHODS. A sample of 87 older adults (M(age) = 83, range = 70–97, 28% male) completed measures of daily stress, cognitive interference, and NA on 6 days within a 14-day period. RESULTS. The measure yielded a single-factor solution with good reliability both between and within persons. At the between-person level, NA accounted for the effects of daily stress on individual differences in cognitive interference. At the within-person level, NA and daily stress were unique predictors of cognitive interference. Furthermore, the within-person effect of daily stress on cognitive interference decreased significantly with age. DISCUSSION. These results support theoretical work regarding associations among stress, NA, and cognitive interference, both across persons and within persons over time.